2006
DOI: 10.1007/s10562-006-0131-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of A-site metal on methane combustion on 2% Pd / AMn1-x Fe x O3 (A = Ba, La, Pr; x = 0.4, 0.6, 1) perovskites

Abstract: Barium, lanthanum, and praseodymium perovskites were prepared by malic acid complexation. Surface areas of the La and Pr perovskites were between 17.1 and 21.6 m 2 g )1 . The moderate low surface areas (5.7 m 2 g )1 ) observed for corresponding barium perovskites were due to the high calcination temperatures. The calcination temperature also affected the shapes and sizes of the perovskite particles. According to SEM images the nanoparticles of the La and Pr perovskites were spherical, whereas those of barium p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Probably, on our structured catalysts, where the catalytic layer completely covers the metal fibers with a thickness of a few micrometers (1 μm of α-Al 2 O 3 from the pre-oxidation treatment plus another 1−2 μm of perovskite), , only surface sulfates are present on the catalyst layer, which are volatile at such temperatures, thus resulting in a limited presence of S-compounds in the 1 and 3 week aged burners (as mentioned before, EDS analysis revealed the presence of only 1% atomic S on the burners compared to the 8% atomic S on the burner aged for 24 h at 600 °C) and consequently in an increase of the catalysts resistance to poison. Moreover, S-compound poisoning is limited when SO 2 is added at high temperature due to the weak adsorption of SO 2 at these temperatures, which additionally arises from the competitive adsorption of H 2 O produced in the oxidation reaction, and the most thermally unstable species desorb at high temperature. , …”
Section: Resultsmentioning
confidence: 99%
“…Probably, on our structured catalysts, where the catalytic layer completely covers the metal fibers with a thickness of a few micrometers (1 μm of α-Al 2 O 3 from the pre-oxidation treatment plus another 1−2 μm of perovskite), , only surface sulfates are present on the catalyst layer, which are volatile at such temperatures, thus resulting in a limited presence of S-compounds in the 1 and 3 week aged burners (as mentioned before, EDS analysis revealed the presence of only 1% atomic S on the burners compared to the 8% atomic S on the burner aged for 24 h at 600 °C) and consequently in an increase of the catalysts resistance to poison. Moreover, S-compound poisoning is limited when SO 2 is added at high temperature due to the weak adsorption of SO 2 at these temperatures, which additionally arises from the competitive adsorption of H 2 O produced in the oxidation reaction, and the most thermally unstable species desorb at high temperature. , …”
Section: Resultsmentioning
confidence: 99%
“…272 Certain authors directly dispersed Pd over perovskite surface. Koponen et al investigated 2%Pd/AMn 1−x Fe x O 3 catalysts (A = Ba, La, Pr; x = 0.4, 0.6, 1) 274 and reported that methane conversion increases in the order La > Pr > Ba, and the highest resistance to SO 2 poisoning is obtained with the 2%Pd/LaMn 0.4 Fe 0.6 O 3 catalyst.…”
mentioning
confidence: 99%
“…The present investigation also confirms that the Pd 2+ and Ag + can be reduced by the argon glow discharge plasma, according to the XPS analyses. Because the active palladium species for methane combustion is PdO [2][3][4][5][6][7][8][9][10][11], the plasma reduced catalysts were calcined to generate the PdO species. Figure 1 shows the XRD patterns of the C-Pd-M/HZSM-5 catalysts.…”
Section: Characterization Of the Plasma Treated Samplesmentioning
confidence: 99%
“…It thus attracts more and more attentions recently [1][2][3][4][5][6][7][8]. Among all the hydrocarbons, methane combustion is normally used as the model reaction for the catalytic combustion investigations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation